Spatial autoregressive poisson modelling of poverty count in the Philippines - Bañez, John Erwin S. (2006)
Abstract (Several models involving spatial Poisson Autoregression were used on discrete response (poverty count) employing the backfitting algorithm. Results were compared to OLS. The MAPE strongly improved with the introduction of dummy variables for regional membership).